2007
DOI: 10.1200/jco.2007.11.1666
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Infusional High-Dose Fluorouracil (HD-FU), HD-FU Plus Folinic Acid (HD-FU/FA), or HD-FU/FA Plus Biweekly Cisplatin in Advanced Gastric Cancer: Randomized Phase II Trial 40953 of the European Organisation for Research and Treatment of Cancer Gastrointestinal Group and the Arbeitsgemeinschaft Internistische Onkologie

Abstract: Weekly infusional FU/FA plus biweekly Cis is effective and safe in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 22 publications
(20 reference statements)
1
20
1
6
Order By: Relevance
“…For the first-line treatment of GC, it has been shown that combination chemotherapy is, in principle, more efficacious than monotherapy [12,18,19]. It should be noted that the benefit observed in the Cochrane review was rather marginal [hazard ratio (HR) for survival of 0.82; 95 % CI 0.74-0.90].…”
Section: Methodsmentioning
confidence: 99%
“…For the first-line treatment of GC, it has been shown that combination chemotherapy is, in principle, more efficacious than monotherapy [12,18,19]. It should be noted that the benefit observed in the Cochrane review was rather marginal [hazard ratio (HR) for survival of 0.82; 95 % CI 0.74-0.90].…”
Section: Methodsmentioning
confidence: 99%
“…7 During the past decades, a large number of chemotherapy regimens including 5-fluorouracil (5-FU) and cisplatin (CF), epirubicin, cisplatin and infused 5-FU (ECF) or docetaxel, cisplatin and 5-FU (DCF) regimens have been tested in clinical studies 6,[8][9][10][11][12][13] ; however, the additional survival advantage yielded by these combination therapies appears to be marginal. As a result, there is still no internationally accepted standard of care, and uncertainty remains regarding the choice of the regimen.…”
mentioning
confidence: 99%
“…Although systemic chemotherapy has a proven palliative role in patients with AGC, significantly improving quality of life and prolonging survival compared to best supportive care alone 6 ; the prognosis of patients in this setting remains dismal with overall 5-year survival rate ranging from 10 to 15% in the Western countries, Japan and Korea. 7 During the past decades, a large number of chemotherapy regimens including 5-fluorouracil (5-FU) and cisplatin (CF), epirubicin, cisplatin and infused 5-FU (ECF) or docetaxel, cisplatin and 5-FU (DCF) regimens have been tested in clinical studies 6,[8][9][10][11][12][13] ; however, the additional survival advantage yielded by these combination therapies appears to be marginal. As a result, there is still no internationally accepted standard of care, and uncertainty remains regarding the choice of the regimen.…”
mentioning
confidence: 99%
“…Given the large numbers of trials and the many different comparisons in the trials retrieved, the gi dsg made an a posteriori decision to focus on the individual contributions of fluoropyrimidines 20,24,25,28,[32][33][34][35][36][37][38][39][40] , platinum agents 9,23,26,30,36,[41][42][43][44][45] , anthracyclines 34,46 -50,79 , taxanes 22,51,52 , and irinotecan 9,53 . The dsg also decided to determine whether the available evidence supports the regimens that are currently in common use in Ontario 21,24,25,36,48,[55][56][57][58] and to determine the contribution of targeted therapies 59,80 .…”
Section: Resultsmentioning
confidence: 99%
“…This recommendation is based on results of a meta-analysis of eight randomized controlled trials (rcts) 9,23,25,26,30,[42][43][44] that indicated a significant survival benefit for chemotherapy including a platinum agent compared with the same chemotherapy without a platinum agent [hazard ratio (hr): 0.74; 95% confidence interval (ci): 0.65 to 0.84; p < 0.00001]. Many of those rcts were small or phase ii trials (or both).…”
Section: Recommendations and Key Evidencementioning
confidence: 99%